Developing waqf land through crowdfunding-waqf model (CWM): the case of Malaysia - Mohd Thas Thaker, Mohamed Asmy; Allah Pitchay, Anwar (Emerald Publishing Limited, 2018)
Purpose – This paper aims to attempt to offer a viable alternative model of source of financing to develop waqf land, which is known as crowdfunding-waqf model (CWM). Design/methodology/approach – The extant literature on the financing constraints faced by waqf institution in developing waqf land, and crowdfunding have been reviewed critically and used in the attempt of proposing an alternative model. Findings – The paper has developed CWM as a source of financing for waqf institution in Malaysia. This model is expected to provide waqf institution in Malaysia to meet their liquidity constraint in developing waqf land. It also involves an involvement of crowdfunding platform. Research limitations/implications – The paper is based on conceptual explorations of literature in the area of waqf and crowdfunding. This is a conceptual paper, so it did not use any empirical analysis. Practical implications – The findings of this paper will provide waqf institution with an alternative source of financing to develop waqf land. The present study also has implications for government and policymakers. By involving crowdfunding, it helps the government to reduce its expenses for the development of waqf land in Malaysia. Originality/value – This paper offers an additional literature on waqf and crowdfunding especially from the Malaysian context. The paper proposes a viable alternative model for waqf institution as a source of financing by using crowdfunding, to develop waqf land. This model incorporates donation-based crowdfunding model and reward-based crowdfunding model. This model is different with the existing way of raising Cash waqf, which is conducted also via online basis by financial institutions and state government agencies. Later, the collected Cash waqf fund is transformed into illiquid assets such as building of hospitals, educational institutions and purchasing machinery and assets. However, the nature of proposed model in this study is to assist waqf institution to develop waqf land. Crowdfunding model is used to raise fund to develop waqf land in Malaysia. The fund collected via crowdfunding model is based on donation and reward based, not based on the nature of Cash waqf.